Understanding how the crowded interior of cells stabilizes DNA/DNA and DNA/RNA hybrids–in silico predictions and in vitro evidence - Harve, K.; Lareu, Ricky R.; Rajagopalan, R.; Raghunath, M. (Oxford University Press, 2010)
Amplification of DNA in vivo occurs in intracellular environments characterized by macromolecular crowding (MMC). In vitro Polymerase-chain-reaction (PCR), however, is non-crowded, requires thermal cycling for melting of DNA strands, primer-template hybridization and enzymatic primer-extension. The temperature-optima for primer-annealing and extension are strikingly disparate which predicts primers to dissociate from template during extension thereby compromising PCR efficiency. We hypothesized that MMC is not only important for the extension phase in vivo but also during PCR by stabilizing nucleotide hybrids. Novel atomistic Molecular Dynamics simulations elucidated that MMC stabilizes hydrogen-bonding between complementary nucleotides. Real-time PCR under MMC confirmed that melting-temperatures of complementary DNA–DNA and DNA–RNA hybrids increased by up to 8°C with high specificity and high duplex-preservation after extension (71% versus 37% non-crowded). MMC enhanced DNA hybrid-helicity, and drove specificity of duplex formation preferring matching versus mismatched sequences, including hair-pin-forming DNA- single-strands.